Crevice corrosion at welded spacers of stainless steel double pipeline. Case study - Marjanowski , Jan (Instal, 2022)
Pipe in pipe (PIP) constructed from DIN 1.4301/1.4307 stainless steel was used for neutral product (chocolate) transport at 58oC in a food plant. Stainless steel spacers were welded along the internal pipeline. Corrosion rate increased because iron ions dissolved and dispersed in water were introduced to the outer stainless steel pipeline from carbon steel installation and carbon steel buffer tank. Rust patches were formed in all pockets present in the pipeline jacket because of iron ions content in water. Local chlorides concentration increased due to adsorption in rust so that crevice and pitting effects were very high. Heating water circulating between external and internal pipeli ne effected high number perforations of both lines in 20 days after production started. Perforations were localised mainly in crevices present between stainless steel spacers and both pipelines. Preventive measures against corrosion were suggested.
Keywords: stainless steel corrosion; crevice corrosion; pitting corrosion; stainless steel pipe in pipe; welded stainless steel spacers; depolarization with Fe3+ ions